Genetic polymorphism in domain I of the apical membrane antigen-1 among Plasmodium knowlesi clinical isolates from Peninsular Malaysia - Fong, Mun Yik; Wong, Shen Siang; De Silva, Jeremy Ryan; Lau, Yee Ling (Elsevier, 2015)
The simian malaria parasite Plasmodium knowlesi is now recognized as a species that can cause human malaria. The first report of large scale human knowlesi malaria was in 2004 in Malaysia Borneo. Since then, hundreds of human knowlesi malaria cases have been reported in Southeast Asia. The present study investigates the genetic polymorphism of P. knowlesi DI domain of the apical membrane antigen-1 (AMA-1), a protein considered as a promising vaccine candidate for malaria. The DI domain of AMA-1 gene of P. knowlesi clinical isolates from Peninsular Malaysia was amplified by PCR, cloned into Escherichia coli, then sequenced and analysed. Ninety-seven DI domain sequences were obtained. Comparison at the nucleotide level against P. knowlesi strain H as reference sequence showed 21 synonymous and 25 nonsynonymous mutations. Nonetheless, nucleotide sequence analysis revealed low genetic diversity of the DI domain, and it was under purifying (negative) selection. At the amino acid level, 26 different haplotypes were identified and 2 were predominant haplotypes (H1, H2) with high frequencies. Phylogenetic analysis revealed that the 26 haplotypes could be clustered into 2 distinct groups (I and II). Members of the groups were basically derived from haplotypes H1 and H2, respectively. (C) 2015 Elsevier B.V. All rights reserved.